2004
DOI: 10.1007/bf03166435
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser ablation of gold at 1064 nm and 532 nm

Abstract: A Nd:Yag laser, 9 ns pulse duration and 900 mJ maximum pulse energy, operating at the 1 064 nm fundamental wavelength and 532 nm second harmonic, is employed to irradiate Au targets placed in vacuum by using single laser pulses. The laser ablation is investigated in terms of ablation threshold, ablation yield, crater production and angular emission. The produced plasma emits ions at different charge state, from 1+ up to 6+, with supersonic velocity and kinetic energies up to about 3 keV, as demonstrated by tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The measured fast-electron kinetic energies, of the order of 2-3 keV, are in good agreement with previous measurements on gold, which demonstrate that fast electrons have kinetic energy ∼5 keV [14]. Moreover, these results are also in agreement with X-ray measurements performed at LNS, demonstrating that X-ray energy of ∼5 keV can be produced by plasma-laser as a process of primary electron bremsstrahlung effect [15].…”
Section: Discussionsupporting
confidence: 89%
“…The measured fast-electron kinetic energies, of the order of 2-3 keV, are in good agreement with previous measurements on gold, which demonstrate that fast electrons have kinetic energy ∼5 keV [14]. Moreover, these results are also in agreement with X-ray measurements performed at LNS, demonstrating that X-ray energy of ∼5 keV can be produced by plasma-laser as a process of primary electron bremsstrahlung effect [15].…”
Section: Discussionsupporting
confidence: 89%
“…In a similar vein, Hleb and Lapotko noted that NRs with an absorption cross section maximum near 750 nm were surprisingly more easily damaged by 532 nm laser pulses than with 750 nm laser pulses . It should be noted that the threshold intensities observed for 100 nm Au NPs were still well below the ablation threshold of bulk Au, reported by Torrisi et al, to be 10 J/cm 2 …”
Section: Discussionmentioning
confidence: 61%
“…61 It should be noted that the threshold intensities observed for 100 nm Au NPs were still well below the ablation threshold of bulk Au, reported by Torrisi et al, to be 10 J/cm 2 . 72 The decrease in scattered intensity with increasing laser pulse fluence in Figure 1a could be due to one of two factors: (1) a reduction in the number of scattering NPs (possibly caused by some fraction of the NPs being shattered by the laser pulse) or (2) efficiency of scattering by each NP (possibly caused by a reduction in size or change in shape). For the moderate laser fluence exposures of 31 mJ/cm 2 for the 60 nm and 72 mJ/cm 2 for the 30 nm NPs, DMA results showed that the number of NPs was relatively unchanged by the pulse, whereas DLS results in Figure 1a showed a decrease in scattering intensity, and UV−vis spectroscopy in Figure 4b showed a decrease in absorption.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The comparison of pulsed laser ablation at 1 064 nm and 532 nm demonstrates that the ablation threshold is higher at the infrared radiation and the total etching yield (i.e. crater volume) is higher at the visible one [3]. SEM and profilometer analysis of the craters presented in [14] show that the crater dimensions increase proportionally to the laser fluence for both the laser systems.…”
Section: Discussionmentioning
confidence: 99%
“…The third one shows etching rates (of the order of µg/pulse). Comparison of the pulsed laser ablation of the gold at first (1 064 nm) and second harmonics (532 nm) demonstrates that the ablation threshold due to the visible radiation is lower with respect to the infrared one by a factor 2, in contrast to the total yield is higher by about a factor 5 for the visible radiation [3].…”
Section: Craters At Low Laser Intensitiesmentioning
confidence: 99%